Solution of the stabilization of satellite problem with bioinspired optimization methods - A. V. Panteleyev; N. M. Orlovskaya (Научный вестник МГТУ ГА, 2016)
This paper presents bioinspired global optimization methods to solve the problem of finding the optimal program control of bundle of trajectories of nonlinear deterministic systems. It considers four bioinspired global optimization methods: Shuffled Frog Leaping Algorithm, Weed Colonization, Glowworm Swarm Optimization and Cuckoo search. The effectiveness of the proposed algorithms is researched with the software complex, formed in C#. The solution of stabilization of satellite problem is presented.